The Iraqi sovereignty after 2003 from a constructive perspective - hassan , haishim abdulmotalb (The International and Political Journal, 2025)
State sovereignty means its ability to impose its authority in its territory and its freedom to manage its internal and external affairs. Sovereignty is linked to the national security of the state and is considered a manifestation of it. Equality in sovereignty among states preserves their rights and duties with legal equality between them according to the principles of international organization. The structural perspective provides a distinctive understanding of international interactions by presenting security as a social structure that goes back to the identity of the state that formulates its interests according to its identity. The occupation of Iraq in 2003 led to the strengthening of sub-identities and their empowerment with their identity extensions across borders in the face of their local competitors in their struggle for power and influence, which made Iraqi sovereignty the focus of sharp interactions between them. Accordingly, national sovereignty and the security data that follow it became at stake.